THE EFFECT OF AUDIT QUALITY, LIQUIDITY, PROFITABILITY AND FIRM SIZE ON THE ACCEPTANCE OF GOING CONCERN OPINION IN TRANSPORTATION COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Hantono (Journal of Research in Business, Economics, and Education, 2020)
This study aims to determine the effect of: 1) Audit Quality, 2) Liquidity, 3) Profitability, 4) Firm Size on the Acceptance of Going Concern Audit Opinions. This type of research is causality. The study population is a transportation company listed on the Stock Exchange in 2014-2018. The research sample used a purposive sampling method of 18 companies. The data used are secondary data obtained from the IDX and data analysis using descriptive statistics and logistic regression. The results showed that audit quality does not affect going concern opinion, liquidity affects going concern opinion, profitability does not affect going concern opinion, firm size influences going concern opinion in financial reporting on transportation companies listed on the Indonesia Stock Exchange in 2014- 2018. The significant value of the omnibus test must be below 0.05 This significant value meets the requirements of the significance level (0.05), thus the hypothesis is accepted. This shows that there is a significant influence of the independent variables simultaneously influencing the dependent variable so that the acceptance of this hypothesis shows that audit quality, liquidity, profitability and firm size on going concern opinion reception influence jointly in financial reporting on transport companies registered at Indonesia Stock Exchange in 2014-2018.